(untitled) (Amman : Manshurat Amanah, 2005)
Commentaries on I'jaz al-Qur'an by Baqillani, Muhammad ibn al-Ṭayyib, d. 1013; Dala'il al-i'jaz by Jurjani,'Abd al-Qahir ibn'Abd al-Rahman, d. 1078?; criticism and interpretation; Koran; language style; comparative study
Keywords: Baqillani, Muhammad ibn al-Tayyib, -- d. 1013.; Jurjani,'Abd al-Qahir ibn'Abd al-Rahman, -- d. 1078?.; Qur'an -- Hermeneutics -- Comparative studies